Corporate and personal income tax declarations - Laszlo Goerke (Center for Economic Studies and ifo Institute (CESifo), 2006)
Decisions by firms and individuals on the extent of their tax payments have generally been treated as separate choices. Empirically, a positive relationship between corporate and personal income tax evasion can be observed. The theoretical analysis in this paper shows that a manager's decision on the firm's behaviour will be independent of his personal preferences if the gain from reducing corporate tax payments is certain, as in the case of tax avoidance. If, however, the firm evades taxes so that the manager's income depends on whether the firm's activities are detected or not, corporate and personal income tax evasion choices cannot be separated.
Keywords: H24; H25; H26; 330